Load transfer mechanism of the composites incorporating nanohybrid shish-kebab structures. (March 2015) - Chen, Mingyang; Lu, Zixing
Abstract: In this paper, the load transfer mechanism of the composites incorporating nanohybrid shish-kebab structures is analyzed by an improved shear-lag model. The discontinuity of the matrix and interface, which is introduced by the specific periodical morphology of nanohybrid shish-kebab structure, is incorporated in the newly developed shear-lag model. A satisfying agreement is obtained between the stress distributions derived by the present model and finite element simulation. The "load transfer back" phenomenon is found for the nanohybrid shish-kebab structure, which can be attributed to the redistribution of the axial loads according to the variation of elastic modulus of matrix along the axial direction. Besides, considerable improvement of load transfer efficiency is observed due to the enhancement of the mechanical property of the interface. The parametric study shows that the elastic modulus and morphology of the nanohybrid shish-kebab structure both have pronounced effects on the load transfer characteristics of the composites, while the effect of the van der Waals interaction is very limited.